2014
DOI: 10.1001/jamaoto.2014.2360
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Predicting Gastrostomy Tube Placement in Patients Undergoing Surgery for Upper Aerodigestive Tract Lesions

Abstract: IMPORTANCE Identifying high-risk patients in the preoperative period can allow physicians to optimize nutritional status early for better outcomes after head and neck cancer resections. OBJECTIVE To develop a model to predict preoperatively the need for gastrostomy tube (G-tube) placement in patients undergoing surgery of the upper aerodigestive tract. DESIGN, SETTING, AND PARTICIPANTS This retrospective medical record review included all adult patients diagnosed with head and neck cancers who underwent tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 17 publications
(29 reference statements)
6
33
0
Order By: Relevance
“…In order to better identify those with the greatest need for gastrostomy tube placement, a recent predictive model based on variables available to the surgeon in the pre-operative period was developed to identify patients at high risk of G-tube placement in the post-operative period. The goal of this model was to identify high risk patients early, prior to resection, in order to avoid poor outcomes potentially related to poor nutritional status [3]. The model gives each patient a predictive probability score for placement of a G-tube in the post-operative period by entering the presence or absence of several pre-operative variables into the predictive equation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better identify those with the greatest need for gastrostomy tube placement, a recent predictive model based on variables available to the surgeon in the pre-operative period was developed to identify patients at high risk of G-tube placement in the post-operative period. The goal of this model was to identify high risk patients early, prior to resection, in order to avoid poor outcomes potentially related to poor nutritional status [3]. The model gives each patient a predictive probability score for placement of a G-tube in the post-operative period by entering the presence or absence of several pre-operative variables into the predictive equation.…”
Section: Introductionmentioning
confidence: 99%
“…The established MST for identifying patients at risk of malnutrition (Ferguson et al, 1999a) was for the first time found to be associated with predicting proPEG in the low risk group of patients. As the MST identifies patients with baseline weight loss this supports other studies which have identified baseline weight loss to be predictive of proPEG (Beaver et al, 2001;Gardine et al, 1988;Mangar et al, 2006;Mays et al, 2014;Orphanidou et al, 2011). Finally a positive p16 status was also found to be predictive of proPEG in the low risk group of patients.…”
Section: Appropriate Access To Nutrition Caresupporting
confidence: 82%
“…The study by Lango et al (2016) was completed in patients receiving (chemo) radiotherapy but had a small sample in comparison (n=84). Pre-treatment weight loss was the only other patient factor supported by a number of level III and IV studies (Beaver et al, 2001;Gardine et al, 1988;Mangar, Slevin, Mais, & Sykes, 2006;Mays, Moustafa, Worley, Waltonen & D'Agostino, 2014;Orphanidou et al, 2011).…”
Section: Predictors Of Tube Feedingmentioning
confidence: 91%
See 2 more Smart Citations